Local Antibiotic Delivery Systems: Current and Future Applications for Diabetic Foot Infections. (March 2018) - Markakis, Konstantinos; Faris, Alan Robert; Sharaf, Hamed; Faris, Barzo; Rees, Sharon; Bowling, Frank L.
Foot infections are common among diabetic patients with peripheral neuropathy and/or peripheral arterial disease, and it can be the pivotal event leading to a minor or major amputation of the lower extremity. Treatment of diabetic foot infections, especially deep-seated ones, remains challenging, in part because impaired blood perfusion and the presence of biofilms can impair the effectiveness of systemic antibiotics. The local application of antibiotics is an emerging field in the treatment of diabetic foot infections, with demonstrable advantages. These include delivery of high concentrations of antibiotics in the affected area, limited systemic absorption, and thus negligible side effects. Biodegradable vehicles, such as calcium sulfate beads, are the prototypical system, providing a good elution profile and the ability to be impregnated with a variety of antibiotics. These have largely superseded the nonbiodegradable vehicles, but the strongest evidence available is for calcium bead implantation for osteomyelitis management. Natural polymers, such as collagen sponge, are an emerging class of delivery systems, although thus far, data on diabetic foot infections are limited. There is recent interest in the novel antimicrobial peptide pexiganan in the form of cream, which is active against most of the microorganisms isolated in diabetic foot infections. These are promising developments, but randomized trials are required to ascertain the efficacy of these systems and to define the indications for their use. Currently, the role of topical antibiotic agents in treating diabetic foot infections is limited and outside of routine practice.